Ancient DNA preserved in small bone fragments from the P.W. Lund collection - Seersholm, Frederik V.; Hansen, K.L.; Heydenrych, Matthew; Hansen, A.J.; Bunce, Michael; Allentoft, Morten (WILEY, 2021)
The Lund collection is one of the oldest subfossil collections in the world. The vast assemblage of subfossils was collected in the 1830s and 1840s by Peter Wilhelm Lund in Lagoa Santa, Brazil, and was shipped to Copenhagen in 1848, where it was stored in various locations around the city with little attention for the future preservation of the collection. So far, successful genetic research on the material collected by Lund has been limited to two samples of human petrous bone. However, less is known about the preservation conditions of the vast amounts of small and fragmentary bones stored in the collection. To address this, we studied ancient DNA from bulk bone samples of approximately 100 bone fragments from the P.W. Lund collection from boxes with varying degrees of physical preservation conditions. Using bulk bone metabarcoding, we found a high species diversity in all samples. In total, we identified 17 species, representing 11 mammals, two birds, one fish, and three frogs. Of these, two species are new to the collection. Collectively, these results exhibit the potential of future genetic studies on the famous P.W. Lund collection and suggest that the effects of poor storage conditions are probably negligible compared with the long-term in situ degradation that specimens undergo before excavation.